RISK MANAGEMENT OF AGRICULTURAL FLOODS - Skakavac, Zdravko; Njegomir, Vladimir; Pejanović, Ljubo; Skakavac, Andja (Economics of Agriculture, 2017)
Agricultural production in Serbia accounts for the largest part of the gross domestic product and can be an economic backbone and the main driver of the domestic food industry and exports, primarily because of its potential such as arable land and a long tradition of agricultural production in these regions. However, numerous risks threaten its stability. The focus of our research is agricultural flooding. The set-up aim of the research is an examination of the causes and consequences of agricultural felds in order to holistically research the current problem. In order to achieve the target, in the paper we will analyze the realization of floods in Serbia, followed by subjective and objective factors of the realization of floods, or the realization of floods caused by human or natural forces and then we will point out the economic consequences of the execution of agricultural floods as well as the application of preventive measures and measures of fnancing the resulting economic consequences.